2004
DOI: 10.1128/aac.48.1.104-109.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Enzyme Immunoassay for Measuring Plasma and Intracellular Nevirapine Levels in Human Immunodeficiency Virus-Infected Patients

Abstract: We have developed an enzyme immunoassay to measure nevirapine (NVP) in plasma and peripheral blood mononuclear cells. Anti-NVP polyclonal antibodies were raised in rabbits by using a synthetic NVP derivative coupled to keyhole limpet hemocyanin as the immunogen, and the enzyme tracer was prepared by chemically coupling the NVP derivative with acetylcholinesterase. These reagents were used to develop a sensitive competitive enzyme immunoassay performed in microtitration plates with a 100-pg ml ؊1 limit of detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Competitive ELISA-RTV, NVP, and LPV were quantified by competitive ELISA as previously described (15,16). Results were expressed as nanomole of HIV drugs/10 6 cells.…”
Section: Hiv Drugs In Cultured Human Adipocytes 2239mentioning
confidence: 99%
See 2 more Smart Citations
“…Competitive ELISA-RTV, NVP, and LPV were quantified by competitive ELISA as previously described (15,16). Results were expressed as nanomole of HIV drugs/10 6 cells.…”
Section: Hiv Drugs In Cultured Human Adipocytes 2239mentioning
confidence: 99%
“…This result strongly suggested that accumulation of the drugs into preadipose cells could be regulated via MDR transporters. We have previously shown that the antibodies used in the ELISAs are specific for the native form of the drugs and do not recognize metabolic forms (15,16). In addition, HPLC-UV analysis indicated that the PIs stored into adipose cells displayed a chemical profile identical to the native form of the PIs (not shown).…”
Section: Hiv Drugs Enter and Accumulate Intomentioning
confidence: 99%
See 1 more Smart Citation
“…Assays were performed in 96-well microtiter plates coated with mouse monoclonal anti-rabbit IgG antibodies (Bertin Pharma, Montigny le Bretonneux, France) as previously described [16]. After washing the coated microtiter plate, the assay was performed in a total volume of 150 μL.…”
Section: Enzyme Immunoassaymentioning
confidence: 99%
“…Enzyme immunoassays were performed in 96-well microtiter plates coated with mouse monoclonal anti-rabbit immunoglobulin G antibodies (Jackson, West Grove, PA), as described previously (3). After the coated microtiter plate was washed, the assay was performed in a total volume of 150 l. The following were successively added to each well: 50 l of calibrator, quality control, buffer, or sample; 50 l of enzyme tracer (2 Ellman units/ml); and 50 l of diluted antiserum.…”
Section: Reagentsmentioning
confidence: 99%